HUBUNGAN KOMUNIKASI ANTARPRIBADI DENGAN MOTIVASI KERJA KARYAWAN PADA DIVISI PEMASARAN REPUBLIK INSULA - Akbar, Aulia (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Interpersonal communication as a form of behavior change can be very effective to very ineffective, and at the time of the communication could be worse and other times it could be better and know the intensity of interpersonal communication between management and employees subordinate divisions among Republican Insula. Permasalahan discussed how strong is the relationship between leadership and Interpersonal Communication with a subordinate employee motivation in the marketing division of the Republic of Insula, the method used is a quantitative approach that is both explanatory and marketing Division employees took respondents Czech Republic Insula Insula in offices located in the South to be a population Cipete in this study. The result was a correlation coefficient of 0.855 was obtained, namely at the level of relationship is very strong. This suggests a strong relationship between the variables Relationship Between Leadership and Interpersonal Communications Shirts With Work Motivation In Marketing Division of the Republic of South Insula in Cipete office.